2017
DOI: 10.1186/s40490-017-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the variation in wood density of New Zealand-grown Douglas-fir

Abstract: Background: Wood density is an important property that affects the performance of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) timber. In order to develop strategies to achieve certain end-product outcomes, forest managers and wood processors require information on the variation in wood density across sites, among trees within a stand and within trees. Therefore, the aim of this study was to develop models explaining the variation in outerwood density among sites and among trees within a stand, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
1
15
0
2
Order By: Relevance
“…Various other factors can also impact the properties of wood in trees, including site, soil, or climate (Zobel and van Buijtenen 1989). A review paper focused on Sitka spruce by Macdonald (2002) found that wood density decreases with increasing site productivity; this was recently confirmed in radiata pine (Kimberley et al 2015) and Douglas fir (Kimberley et al 2017) as well. The effect of site on dynamic MOE in young radiata pine was also found to be substantial (Watt et al 2006;Lasserre et al 2008).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Various other factors can also impact the properties of wood in trees, including site, soil, or climate (Zobel and van Buijtenen 1989). A review paper focused on Sitka spruce by Macdonald (2002) found that wood density decreases with increasing site productivity; this was recently confirmed in radiata pine (Kimberley et al 2015) and Douglas fir (Kimberley et al 2017) as well. The effect of site on dynamic MOE in young radiata pine was also found to be substantial (Watt et al 2006;Lasserre et al 2008).…”
Section: Introductionmentioning
confidence: 85%
“…Most authors seem to agree that those changes are a consequence of wider tree rings from accelerated growth after the thinning. A small number of studies reported no change in density after early respacing or thinning-in Sitka spruce , Douglas fir (Kimberley et al 2017), or black spruce (Picea mariana (Mill.) BSP) (Vincent et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…), and black spruce (Picea mariana (Mill.) B.S.P) all exhibit SG radial trends where SG is high near the pith, decreases in the transition wood, and then increases in the outerwood [19,40,41]. For loblolly pine, the reason for the low SG near the pith is due to the low proportion of latewood to earlywood tracheids and reduced cell wall thicknesses, as well as lower latewood SG [13,42].…”
Section: Introductionmentioning
confidence: 99%
“…In the southern pines, SG increases from pith to bark, while at the same time, microfibril angle decreases from pith to bark [70,71]. For Douglas-fir, the microfibril angle trend is the same as the southern pines, but SG decreases from pith to bark for approximately 10 years, then it gradually increases [67]. Thus, the relationships between SG and MOE and MOR is not as strong as what was reported previously for southern pine, and they mirror results others have found for Douglas-fir [72].…”
Section: Discussionmentioning
confidence: 99%
“…For both models, the quadratic model form instead of a linear model was used because of the differences in the radial variation trends for wood properties of Douglas-fir. Wood density decreases for approximately 8 years from pith to bark and then increases, whereas stiffness and strength increases from pith to bark because of decreasing microfibril angle [67]. Thus, for samples near the pith, a lower density value does not necessarily mean a decrease in wood stiffness or strength.…”
Section: Wood Property Calibration and Prediction Of Wood Propertiesmentioning
confidence: 97%